GAMBARAN NILAI HEMATOKRIT PADA PASIEN TUBERCOLOSIS DENGAN MENGGUNAKAN DARAH VENA DI RUMAH SAKIT UMUM DAERAH LABUANG BAJI MAKASSAR - Rahmat Saleh; Tary Uswatun Hasanah; Dita Ellyana Artha; Aisyah Aisyah; Suharsih Thahir (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Tuberculosis is one of the diseases that can be transmitted through the air caused by the bacteria Mycobacterium tubercolosis. The purpose of this study was to determine the hematocrit picture in tuberculosis patients. The method used in this study is descriptive quantitative. The research sample was examined directly using the macrohematocrit method. The procedure in this study includes several stages, namely the pre-analytical, analytical, and post-analytical stages. In the pre-analytical stage, the researcher prepared the tools and materials to be used. Analytical stage, at this stage the researcher took samples and prepared samples, Post-analytical stage, at this stage the researcher calculated the normal hematocrit value. Based on the results of the study, it showed that there were 4 people with low hematocrit values ​​and 4 people with high hematocrit values. While the hematocrit value in men had a low hematocrit value of 2 people and a high hematocrit value of 2 people, while in women the hematocrit value was low as many as 2 people and a high hematocrit value of 2 people. In this study, there was no difference in hematocrit values ​​between men and women.